Can green patents reduce carbon emission intensity?—An empirical analysis based on China’s experience - Wang, Na; Yu, Huifang; Shu, Yalin; Chen, Zhao; Li, Tiechen (Frontiers in Environmental Science, 2022)
Achieving “peak carbon” and “carbon neutrality” and designing energy conservation and emission reduction policies in China require giving full play to the effect of green technology innovation. This paper uses annual data from 1993 to 2020 in China, including the number of green invention patents and green utility model patents, and tests the long-term and short-term effects of green innovation on carbon emission intensity by constructing an ARDL model. The results show that the effect of green invention patents and green utility model patents on CO2 emission intensity is different. Specifically, green invention patents contribute to reducing carbon emission intensity in the short term but act as a barrier in the long term. Green utility model patents suppress carbon emission intensity in the short and long terms. In addition, adjustment of the industrial structure characterized by “shrinking the secondary sector and developing the tertiary sector” has the most excellent effect on reducing carbon emission intensity in the short term. The relative energy price’s carbon emission reduction effect is weaker than the industrial structure. Foreign direct investment and non-fossil energy consumption increase carbon emission intensity in the short term. In the long term, increasing the proportion of non-fossil energy is crucial to reducing carbon emission intensity. The carbon emission reduction effect of energy price is insignificant, and foreign direct investment is not conducive to carbon emission reduction. Finally, this paper analyzes the policy implications of the empirical results and proposes recommendations for reducing China’s CO2 emission intensity accordingly.